Police organizational cultures and patrol practices - Hassell, Kimberly D. (Criminal justice (LFB Scholarly Publishing LLC), 2006)
Hassell studies police organizational cultures and patrol practices through close participant observation in a large, municipal Midwestern police department. Her work uncovers that organizational cultures are formed at the precinct level. Police patrol practices, concomitantly, vary markedly within this police organization at the precinct level of analysis. Not only were these patterns observed, but police patrol officers overwhelmingly agree that the organizational cultures and police patrol practices vary at the sub-organizational level of the precinct. Furthermore, this study shows some support for David Klinger's (1997) causal model of police behavior ("Negotiating Order in Patrol") but the overall utility of the model, in this context, is weak